IMPLEMENTATION OF LOGISTICS 4.0 IN A COMPANY’S SUPPLY CHAIN - Porto, João Victor Rodrigues; Casagrande , Diego José (Revista Interface Tecnológica, 2022)
This article aims to show the efficiency and benefits provided by logistics 4.0 in the supply chain of companies. The technological scenario is becoming increasingly promising and therefore requires companies to adapt to the restructuring of production, in order to minimize costs, without losing quality and customer satisfaction, and mirroring the concepts of industry 4.0 for the logistics sector. it is fundamental. In order to achieve the proposed objectives, a case study was prepared through a questionnaire in the alpha company, where it was corresponded by two managers of the area, in order to identify if this implementation is already present in the branch, if it has knowledge and of the benefits and challenges. generated by it. The results obtained in this work confirm the mentioned theories, since this implementation minimizes bottlenecks and meets the high level of demand provided by the tools included in this concept.